Structure of a light-activated LOV protein dimer that regulates transcription in Neurospora crassa - Vaidya, Anand T. (2011)
Light oxygen or voltage (LOV) domains are widely represented signaling modules in bacteria, archea, protists, plants and fungi. The Neurospora crassa LOV protein VIVID (VVD) allows adaptation to constant or increasing light levels and proper entrainment of circadian rhythms. The crystal structure of the fully light-adapted VVD dimer reveals the mechanism by which light driven conformational change alters oligomeric state. Photo-induced formation of a cysteinyl-flavin adduct generates a new hydrogen bond network that releases the N-terminus from the protein core and restructures an acceptor pocket for its binding on the opposite subunit. Substitution of residues key to the monomer/dimer switch have profound effects on light adaptation in Neurospora. The VVD dimerization mechanism provides the molecular details for how a large family of photoreceptors converts light responses to alterations in protein interactions.